PRMT5 confers lipid metabolism reprogramming, tumour growth and metastasis depending on the SIRT7-mediated desuccinylation of PRMT5 K387 in tumours - Yuan Hong-feng; Zhao Man; Zhao Li-na; Yun Hao-lin; Yang Guang; Geng Yu; Wang Yu-fei; Zheng Wei; Yuan Ying; Song Tian-qiang; Niu Jun-qi; Zhang Xiao-dong (Acta Pharmacologica Sinica, 2022)
The protein arginine methyltransferase 5 (PRMT5), which is highly expressed in tumour tissues, plays a crucial role in cancer development. However, the mechanism by which PRMT5 promotes cancer growth is poorly understood. Here, we report that PRMT5 contributes to lipid metabolism reprogramming, tumour growth and metastasis depending on the SIRT7-mediated desuccinylation of PRMT5 K387 in tumours. Mass spectrometric analysis identified PRMT5 lysine 387 as its succinylation site. Moreover, the desuccinylation of PRMT5 K387 enhances the methyltransferase activity of PRMT5. SIRT7 catalyses the desuccinylation of PRMT5 in cells. The SIRT7-mediated dessuccinylation of PRMT5 lysine 387 fails to bind to STUB1, decreasing PRMT5 ubiquitination and increasing the interaction between PRMT5 and Mep50, which promotes the formation of the PRMT5- Mep50 octamer. The PRMT5-Mep50 octamer increases PRMT5 methyltransferase activity, leading to arginine methylation of SREBP1a. The symmetric dimethylation of SREBP1a increases the levels of cholesterol, fatty acid, and triglyceride biogenesis in the cells, escaping degradation through the ubiquitin-proteasome pathway. Functionally, the desuccinylation of PRMT5 K387 promotes lipid metabolism reprogramming, tumour growth and metastasis in vitro and in vivo in tumours.